Perancangan User Experience Web Portal Merdeka Belajar FILKOM menggunakan Metode Design Thinking - Miranda Eristiana; Herman Tolle; Intan Sartika Eris Maghfiroh (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2022)
In 2020, the Indonesian Ministry of Education, Culture, Research, and Technology created a program that is useful for improving self-competence for a student, this program is called